Junior dictionary - Goldsmith, Evelyn (Collins London, 2000)
Especially written to support the language and literacy needs of children aged 6+, this dictionary introduces features such as showing parts of speech (noun, verb, adjective or adverb) and other forms of a word (plurals or past tense of a verb)